2004
DOI: 10.1093/molbev/msh128
|View full text |Cite
|
Sign up to set email alerts
|

Common Pattern of Evolution of Gene Expression Level and Protein Sequence in Drosophila

Abstract: Sequence divergence scaled by variation within species has been used to infer the action of selection upon individual genes. Applying this approach to expression, we compared whole-genome whole-body RNA levels in 10 heterozygous Drosophila simulans genotypes and a pooled sample of 10 D. melanogaster lines using Affymetrix Genechip. For 972 genes expressed in D. melanogaster, the transcript level was below detection threshold in D. simulans, which may be explained either by sequence divergence between the prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
233
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(266 citation statements)
references
References 41 publications
31
233
1
1
Order By: Relevance
“…As an example of this, (Dassanayake et al, 2009) used transcriptome characterization of two species of mangrove to investigate convergent evolution of gene expression. Shared transcriptomic profiles between species may of course be a result of a common evolutionary origin or a joint distribution (Nuzhdin et al, 2004). However, in the case of the two mangrove species investigated by Dassanayake et al, this is not likely to explain the pattern seen.…”
Section: Transcriptome Characterizationmentioning
confidence: 87%
“…As an example of this, (Dassanayake et al, 2009) used transcriptome characterization of two species of mangrove to investigate convergent evolution of gene expression. Shared transcriptomic profiles between species may of course be a result of a common evolutionary origin or a joint distribution (Nuzhdin et al, 2004). However, in the case of the two mangrove species investigated by Dassanayake et al, this is not likely to explain the pattern seen.…”
Section: Transcriptome Characterizationmentioning
confidence: 87%
“…2c). Extensive (20%) categorical changes in sex-bias class, especially for genes with male-biased expression, were previously reported between D. melanogaster and D. simulans 12,13 . We observed a categorical change in sex-biased expression in 12% of the orthologues between these two species, but the changes were dominated by low magnitude changes between modest sex-biased expression and non-sex-biased categories.…”
mentioning
confidence: 80%
“…Genome-wide measurements have revealed high rates of genetic variation in gene expression (typically 410% of genes) in humans (Enard et al, 2002;Rockman and Wray, 2002;Bray et al, 2003;Lo et al, 2003;Whitney et al, 2003;Morley et al, 2004;Pastinen et al, 2004;Radich et al, 2004), mice (Cowles et al, 2002;Schadt et al, 2003;Shockley and Churchill, 2006), fish (Oleksiak et al, 2002(Oleksiak et al, , 2005, flies (Jin et al, 2001;Wayne and McIntyre, 2002;Meiklejohn et al, 2003;Rifkin et al, 2003;Nuzhdin et al, 2004;Ranz et al, 2004), yeast (Cavalieri et al, 2000;Brem et al, 2002;Townsend et al, 2003;Yvert et al, 2003;Fay et al, 2004), plants (Kirst et al, 2005;Vuylsteke et al, 2005;Lai et al, 2006) and bacteria (Le et al, 2005). Patterns of expression divergence have also been compared between sexes (Jin et al, 2001;Ranz et al, 2003;Gibson et al, 2004), across developmental stages (Rifkin et al, 2003), among tissue types (Enard et al, 2002;Whitehead and Crawford, 2005;Khaitovich et al, 2005a, b) and over different environments (Fay et al, 2004;Landry et al, 2006).…”
Section: Genomic Variation In Gene Expressionmentioning
confidence: 99%
“…For expression patterns driven by positive selection, large differences between species are expected despite little variation within a species. Although this approach does not distinguish between neutral and selected changes, it provides an interesting list of candidate genes for further study Nuzhdin et al, 2004;Gilad et al, 2006a, b). For example, using this ranking system, Gilad et al (2006a, b) showed that a significant fraction of candidate genes identified in a comparison of primate species were transcription factors.…”
Section: Rates Testsmentioning
confidence: 99%